Designing Pediatric Nano-formulations Faces a slew of Obstacles: A Review - Ravi, kaveena26; Kirubha Hari.C K, (Iraqi Journal of Pharmaceutical Sciences, 2024)
Nanotechnology is a fine tool for enhancing drug efficiency. Doses and medication development for Pediatric Population still remains a challenge.The clinical experience gained from treating adults is usually used in pediatric therapies.Although science has proven that children's pharmacokinetics and pharmacodynamics differ from adult.When applied to children, innovative technologies (e.g., nanotechnology) are highly challenging to implement. An optimal formulation has to be in an acceptable dose type where the pediatric patients can accommodate. Due to its complicated existence, comparatively few efforts were made, in particular to establish pediatric Nano-medicines primarily to increase the solubility and stability of sparingly water-soluble liquid formulation. Though many researchers focus on developing adult medications, some new researches are been carried to provide precision medicines to the infants.Inspite of some safety issues nanotechnology have commenced an era of Nano-pediatrics. The possible negative consequences and medical benefits in Pediatric communities are correlated with Nano-formulated drug treatment that is distinct from adults. Incentives in adult market rather than children's needs often lead to pediatric strategies. Drug kinetics design and simulation are also explored to create pediatric Nano-formulation. Nano formulations play a major role in handling pediatric infectious disease and cancer.Many studies aimed to furnish precision medicine for challenging diseases, especially liposomes are imparted Nano formulations are used in the treatment of tumors in new-borns. This article reviews the challenges faced in designing Nano-pediatrics and flourishing studies involved in serving pediatric precision medicines.